Peningkatan Kemampuan Numerasi Dan Ketangguhan Belajar Melalui Pendekatan Pembelajaran Diferensiasi Ditinjau Dari Gaya Belajar Peserta Didik: Peningkatan Kemampuan Numerasi Dan Ketangguhan Belajar Melalui Pendekatan Pembelajaran Diferensiasi Ditinjau Dari Gaya Belajar Peserta Didik - Eka Elia Robiah Adawiah; Eka Firmansyah (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2025)
This study aims to improve student’s numeracy skills and learning resilience through the implementation of differentiated instruction and to analyze the influence of learning styles on learning outcomes. A mixed-method approach with a pretest–posttest design was employed involving Grade XI students of SMKN 1 Binong Subang, assigned to an experimental class and a control class. The experimental class received differentiated instruction based on visual and kinesthetic learning styles, while the control class received conventional instruction. Research instruments included a numeracy test on arithmetic sequences and series as well as a learning resilience questionnaire. Data were analyzed using descriptive statistics, two-way ANOVA, and Pearson correlation. The findings indicate that differentiated instruction significantly improved student’s numeracy skills and learning resilience, whereas learning styles did not exert a meaningful effect either independently or in interaction with the instructional method. These results affirm that differentiated instruction effectively accommodates student diversity while supporting both cognitive and non-cognitive outcomes. Teachers are advised to implement differentiated instruction consistently by emphasizing student’s readiness and learning needs rather than relying solely on learning styles. Further research is suggested to examine the effectiveness of this instructional approach across different subjects or educational levels to strengthen the generalizability of the findings.